Transport and safety systems, approaches, and implementation - Tiwari, Geetam; Mohan, Dinesh 1945- (Springer transactions in civil and environmental engineering, 2021)
This volume addresses a variety of issues on traffic safety policy, ranging from issues of climate change, urban equity, and transport safety, in a broad global and societal context, while retaining situation-specific details. Written by international experts on issues of transportation and traffic safety, it will be of special interest to advanced researchers in the engineering and planning disciplines working on these issues as well as policy makers concerned with setting up institutions and legislations for traffic safety.